2024
DOI: 10.3390/ani14040579
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Silybum marianum Extract, Synbiotics, Omega-3 Fatty Acids, Vitamins, and Minerals: Impact on Biochemical Markers and Fecal Microbiome in Overweight Dogs

Fatemeh Balouei,
Bruno Stefanon,
Elisa Martello
et al.

Abstract: Overweight and obese dogs can develop metabolic dysfunction, characterized by an inflammatory response and involvement of liver functions. If a modulation of the gut microbiome and its interaction with the gut–liver axis is implicated in the development of metabolic dysfunction, exploration becomes necessary. Over the past decade, diverse therapeutic approaches have emerged to target pathogenic factors involved in metabolic dysfunction. This study investigated the impact of a supplement with hepatoprotective a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The gut microbiota forms a symbiotic system with its host, which is established at birth [7], and the host provides a nutrient-rich environment for the gut microbiota that supports the development of diverse microbial communities dwelling in multiple ecological niches [8]. Studies have shown that dietary intervention [9], environmental factors [10], pathogenic bacteria infection [11], circadian rhythm change [12], and the use of dietary supplements [13] can all affect the composition, structure, and function of the gut microbiota. In recent years, the field of research has increasingly involved whether the hibernation rhythm of certain mammals affects their gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota forms a symbiotic system with its host, which is established at birth [7], and the host provides a nutrient-rich environment for the gut microbiota that supports the development of diverse microbial communities dwelling in multiple ecological niches [8]. Studies have shown that dietary intervention [9], environmental factors [10], pathogenic bacteria infection [11], circadian rhythm change [12], and the use of dietary supplements [13] can all affect the composition, structure, and function of the gut microbiota. In recent years, the field of research has increasingly involved whether the hibernation rhythm of certain mammals affects their gut microbiota.…”
Section: Introductionmentioning
confidence: 99%